Keterkaitan presenteeism dan job satisfaction pada pekerja pra-lansia: Menguji peran mediator resilience dan work-health balance: The relationship between presenteeism and job satisfaction in pre-elderly workers: Testing the mediating role of resilience and work-health balance - Listanto, Melvin; Budiarto, Yohanes; Sahrani, Riana (Persona:Jurnal Psikologi Indonesia, 2025)
The high level of job satisfaction in Indonesia does not necessarily indicate the same perception of work across all age groups, especially among pre-elderly workers (aged 45–59 years). This research aims to investigate the relationship between presenteeism and job satisfaction among pre-elderly workers, while also testing the mediating roles of resilience and work- health balance. This research uses a quantitative correlational approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM) analysis technique on data from 146 pre- elderly workers who have experienced presenteeism due to minor illnesses. The findings show that neither dimensions of presenteeism are not directly related to job satisfaction. Although the completing work is positively associated to resilience, resilience was not found to mediate the relationship between presenteeism and job satisfaction. On the other hand, both presenteeism dimensions were related with work-health balance. Work-health balance was found to be a significant mediator only in the relationship between completing work and job satisfaction. These findings highlight the importance role of work-health balance in supporting job satisfaction among pre-elderly workers who practice presenteeism.